Spectrophotometric Determination of Paracetamol in bulk and Pharmaceutical Preparations - Baghdad Science Journal (مجلة بغداد للعلوم, 2015)
A simple, and rapid spectrophotometric method for the estimation of paracetamol has been developed. The methods is based on diazotisation of 2,4-dichloroaniline followed by a coupling reaction with paracetamol in sodium hydroxide medium. All variables affecting the reaction conditions were carefully studied. Beer's law is obeyed in the concentration range of 4-350 ?gml?1 at 490 nm .The method is successfully employed for the determination of paracetamol in pharmaceutical preparations. No interferes observed in the proposed method. Analytical parameters such as accuracy and precision have been established for the method and evaluated statistically to assess the application of the method.